The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s40409-017-0100-4
|View full text |Cite
|
Sign up to set email alerts
|

Envenomation by the red-tailed coral snake (Micrurus mipartitus) in Colombia

Abstract: BackgroundAlthough the red-tailed coral snake (Micrurus mipartitus) is widely distributed in Colombia and its venom is highly neurotoxic and life threatening, envenomation by this species is rare. Therefore, this report may shed some light on the clinical presentation of M. mipartitus bites.Case presentationsHerein, we describe two cases of patients bitten by red-tailed coral snakes, illustrating the clinical presentation of the victims, the outcomes and treatment provided.ConclusionEnvenomation caused by M. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…For instance, the single published account of a Sinomicrurus macclellandi bite indicated that the victim felt nothing until motor issues started developing 6 h after the bite and culminated in lethal respiratory paralysis after 8 h [ 72 ]. Similarly, bites from snakes of the genus Micrurus often exhibit few symptoms besides paralysis [ 73 , 74 , 75 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the single published account of a Sinomicrurus macclellandi bite indicated that the victim felt nothing until motor issues started developing 6 h after the bite and culminated in lethal respiratory paralysis after 8 h [ 72 ]. Similarly, bites from snakes of the genus Micrurus often exhibit few symptoms besides paralysis [ 73 , 74 , 75 ].…”
Section: Introductionmentioning
confidence: 99%
“…The report of this case aims to raise some questions, the most important of which is: is it worth to classify a coral snake as non-venomous, even if you are a specialist? The Brazilian literature [ 6 , 10 , 12 , 13 ] describes accidents with coral snakes as rare, even when cases with non-venomous species are considered. Due to their non-aggressive behavior, most accidents involving coral snakes are the result of incorrect or reckless handling of these snakes, so that hands and fingers are more frequently affected [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, at Universidad del Valle and Fundación Valle del Lilli, researchers have contributed to our knowledge about clinical manifestations of M. mipartitus and B. punctatus snakebites by informing about some clinical cases inflicted by these species (103,104). Likewise, Cañas reported a case of brainstem ischemic stroke after a B. atrox snakebite, evidencing the incidence and importance of cardiovascular complications of bothropic snakebite in Colombia (105).…”
Section: Other Researchesmentioning
confidence: 99%